2017
DOI: 10.4274/tjod.88123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the content and quality of intrapartum care in vaginal births: An example of a state hospital

Abstract: Objective:The purpose of the research was to assess the content and quality of the intrapartum care offered in vaginal births in Turkey, based on the example of a state hospital.Materials and Methods:This cross-sectional study was conducted between January 1st, 2013 and December 31st, 2014 at Aydın Maternity and Children’s Hospital. The study sample consisted of 303 women giving vaginal birth, who were recruited into the study using the method of convenience sampling. Research data were collected with a questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…It was seen in the present study that fundal pressure was applied to a significant percentage (19.9%) of women. However, this rate is lower than previously reported in several studies conducted in India (50.8%) [ 26 ], Turkey (43.3%) [ 41 ], Turkey (72.6%) [ 60 ], Egypt (36.0%) [ 30 ], Ethiopia (39.6%) [ 42 ] and the Philippines (31.2%) [ 19 ]. In many countries, care providers commonly practice fundal pressure during the second stage of labour to help expedite the delivery process and shorten the second stage of labour [ 30 , 61 ].…”
Section: Discussioncontrasting
confidence: 57%
“…It was seen in the present study that fundal pressure was applied to a significant percentage (19.9%) of women. However, this rate is lower than previously reported in several studies conducted in India (50.8%) [ 26 ], Turkey (43.3%) [ 41 ], Turkey (72.6%) [ 60 ], Egypt (36.0%) [ 30 ], Ethiopia (39.6%) [ 42 ] and the Philippines (31.2%) [ 19 ]. In many countries, care providers commonly practice fundal pressure during the second stage of labour to help expedite the delivery process and shorten the second stage of labour [ 30 , 61 ].…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, the use of episiotomy was well controlled (23.2%), and the 3rd degree perineal laceration was very insignificant (2 cases out of 4192). This episiotomy rate is well below other countries, such as Turkey (54.1%) [ 40 ], Nepal (48.8%) [ 43 ], Austria (30.0–39.7%) [ 44 ]. It is interesting to note that our findings show no correlation between episiotomy or perineal laceration and labor satisfaction.…”
Section: Discussionmentioning
confidence: 79%
“…Kamakshi found that about 33% of the participants knew that delivery is possible without pain, but only 18% were satisfied with the procedure. In Turkey, epidural anesthesia rate for women who have vaginal deliveries is 3.3% [ 40 ]. While in the US, the rate is 60.7–83.5% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings can be found in the relevant literature (Swencionis et al, 2012). However, there are also dissimilar findings, and there are also studiesin which the pregnant women were transferred in to the delivery room early or went through labor in a room with many other women (Atis & Rathfisch, 2018; Karaçam et al, 2017). These different results are likely due to the difference between the standard care protocols adopted by the hospitals where the studies were conducted.…”
Section: Discussionmentioning
confidence: 99%